New approaches of genetic analysis for quantitative traits and their applications in breeding - ZHU Jun (浙江大学学报. 农业与生命科学版, 2000)
Recently developed genetic models and their analysis methods are presented. The new models include agronomy trait models, seed quality models, animal models with sex-linked effects, and models for QTL mapping. The new statistical analysis methods are mostly based on mixed linear model approaches for estimating variances and covariances, unbiasedly predicting random effects, analyzing conditional variaces and effets, and composite interval mapping.